Radioemission of the modulated electron beam injected into ionosphere along the geomagnetic field - Anisimov, I.O.; O.I. Kelnyk, O.I. Kelnyk; Yang Yong; Zhao Zheng Yu (Вопросы атомной науки и техники, 2005)
Report contains calculation of the radioemission of semi-restricted thin modulated electron beam injected from the spacecraft board into the ionosphere plasma along the geomagnetic field. Radioemission appears due to the synchronism between the electric current wave of modulated beam and electromagnetic eigenmode of the anisotropic plasma. Radiation pattern for whistlers’ frequencies is formed as a result of the interference between three independent modes with the same frequency and different wavelengths. Consequently, Pointing vector angular dependence is oscillatory at small angles. At larger angles, the radiation pattern has a sharp maximum near the resonant cone. Доповідь містить розрахунок випромінювання тонкого напівобмеженого модульованого електронного пучка, інжектованого з борту космічного апарату в іоносферну плазму вздовж напрямку геомагнітного поля. Радіови¬ промінювання виникає внаслідок синхронізму між парціальною хвилею струму модульованого електронного пучка і власною електромагнітною хвилею анізотропної плазми. Діаграма спрямованості для свистового іапазону формується в результаті інтерференції між трьома модами з однаковою частотою, але відмінними довжинами хвиль. Відповідно кутова залежність вектора Пойнтінга для малих кутів виявляється осцилюючою функцією. Для більших кутів діаграма спрямованості має різкий максимум поблизу резонансного конусу. Доклад содержит расчет излучения тонкого полуограниченного модулированного электронного пучка, инжектируемого с борта космического аппарата в ионосферную плазму вдоль направления геомагнитного поля. Радиоизлучение возникает вследствие синхронизма между парциальной волной тока модулированного элек¬ тронного пучка и собственной электромагнитной волной анизотропной плазмы. Диаграмма направленности для свистового диапазона формируется в результате интерференции между тремя модами с одинаковой частотой, но разными длинами волн. Соответственно, угловая зависимость вектора Пойнтинга является осциллирующей для малых углов. Для больших значений углов диаграмма направленности имеет резкий максимум вблизи резо¬ нансного конуса.